2007
DOI: 10.1534/genetics.107.076885
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 10 S-Class SLF-like Genes in Nicotiana alata Pollen and Its Implications for Understanding the Pollen Factor of the S Locus

Abstract: The S locus of Nicotiana alata encodes a polymorphic series of ribonucleases (S-RNases) that determine the self-incompatibility (SI) phenotype of the style. The pollen product of the S locus (pollen S) in N. alata is unknown, but in species from the related genus Petunia and in self-incompatible members of the Plantaginaceae and Rosaceae, this function has been assigned to an F-box protein known as SLF or SFB. Here we describe the identification of 10 genes (designated DD1-10) encoding SLF-related proteins tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 51 publications
2
60
0
Order By: Relevance
“…As with the Antirrhinum SLFs, variable amino acid positions are not clustered into distinct hypervariable regions but distributed over the sequence. Similar types of binding and transgenic experiments to those performed with Ah SLF-S 2 have also been done with the Petunia SLF alleles and have produced results that are consistent with expectations for pollen S (Sijacic et al, 2004;Hua and Kao, 2006;Hua et al, 2007).Attempts at identifying SLF orthologs in solanaceous species other than Petunia have highlighted one further evolutionary difference between this gene and the S-RNase gene (Wheeler and Newbigin, 2007). Phylogenetic clustering of S-RNases relative to nearly all other plant RNases points to a single common origin for S-RNase-based SI (Igic and Kohn, 2001;Steinbachs and Holsinger, 2002).…”
supporting
confidence: 60%
See 2 more Smart Citations
“…As with the Antirrhinum SLFs, variable amino acid positions are not clustered into distinct hypervariable regions but distributed over the sequence. Similar types of binding and transgenic experiments to those performed with Ah SLF-S 2 have also been done with the Petunia SLF alleles and have produced results that are consistent with expectations for pollen S (Sijacic et al, 2004;Hua and Kao, 2006;Hua et al, 2007).Attempts at identifying SLF orthologs in solanaceous species other than Petunia have highlighted one further evolutionary difference between this gene and the S-RNase gene (Wheeler and Newbigin, 2007). Phylogenetic clustering of S-RNases relative to nearly all other plant RNases points to a single common origin for S-RNase-based SI (Igic and Kohn, 2001;Steinbachs and Holsinger, 2002).…”
supporting
confidence: 60%
“…By comparison, the S-RNases associated with these four Antirrhinum S alleles appear just as expected, with pairwise amino acid identities ranging from 36 to 51%. Levels of nonsynonymous (amino acid-changing, Ka) and synonymous (silent, Ks) substitutions in the DNA sequence are both more than an order of magnitude lower at the Antirrhinum SLF locus than at the cognate S-RNase locus (Table 1; Xue et al, 1996;Zhou et al, 2003;Sassa et al, 2007;Wheeler and Newbigin, 2007). The high level of identity among the Antirrhinum…”
Section: What's Puzzling About the Slf And Sfbs?mentioning
confidence: 99%
See 1 more Smart Citation
“…This question has recently become even more complicated (see section 8) as it appears that proteins originally identified as SLF-like (SLFL), and not involved in GSI, may in fact be true SLF proteins. Chromosome-walking, differential display or degenerate PCR-cloning approaches Wang et al, 2003Wang et al, ,2004Wheeler & Newbigin 2007;Zhou et al, 2003) in the Solanaceae and Plantaginaceae identified a number of SLF-like genes (SLFL) that were linked to the S-locus. These genes were thought not to be involved in self-incompatibility interactions specifically, since they did not show interaction with known S-RNases nor did they exhibit competitive interaction in transgenic assays (Hua et al, 2007;Meng et al, 2011).…”
Section: Protein Interactions Between Slf and S-rnase Proteinsmentioning
confidence: 99%
“…Additional sequence comparisons demonstrated that SLF proteins could be grouped into at least six subclasses. Because Wheeler & Newbigin (2007) identified at least 10 different SLF-like genes in Nicotiana, and because not all of the previously-identified SLFL genes from Petunia inflata were included in the comparative sequence analysis of Kubo et al (2010), it is possible that more than six SLF subclasses are present. As a result of this analysis, a new nomenclature for SLF proteins has been proposed.…”
Section: Collaborative Non-self Recognition By Slf Proteins In Gsimentioning
confidence: 99%